Social Movements Facing Authoritarian-Style Neoliberal Governments: Comparative Positioning Towards Violence in Indonesia and France - Gabriel Facal; Gloria Truly Estrelita (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2020)
Faced with global and systemic crises, neoliberal oriented governments are taking on more authoritarian forms of governance. By using the power of the media, justice, the police, and a set of government technologies, this authoritarian style manifests itself in alternating phases of low-key brutality and crises of ostentatious repression designed to frighten and demoralize opposition social movements. Confronted with these modes of government, the social movements adopt different tactics of mobilization, ranging from direct confrontation to forms of compromise and civil disobedience. With the climate crisis as well as the globalization of social struggles, these movements adopt new political strategies, which question the dichotomy between violence and non-violence. Using a historical and anthropological approach, this paper studies two cases in contemporary Indonesia and France. It shows that the objectives of the groups involved and the national socio-political and cultural background shape the local specificities of these strategies. The comparison, however, reveals similarities at both levels. It shows the persistence and even strengthening of class and oligarchy networks in the implementation of authoritarian-style neoliberal policies. It also points to the respective effectiveness of violent and non-violent tactics in the implementation of militant strategies.